Microbial Agents in Terrorism, Biomarkers, and Public Health Challenges - Orole, Olukayode; Chuku, Aleruchi; Olawuyi, Kayode; Mantu, Eno; Philips, Alexander; Okoli, Chukwuma (The Journal of Experimental Life Science, 2022)
Bioterrorism agents are mostly microorganisms with the capacity to deal explosive and lethal harm to humans, animals, and food crops. These microorganisms spread in the form of gases, whole organisms, or products of secondary metabolism of microorganisms. Classification of the agents is into three categories based on the ease of dissemination and end effects on a living population. While most health institutions are equipped to take care of sick people and treat suspected cases of infections, these institutions lack basic means of identifying bioterrorism acts. Special diagnostic equipment to identify causal organisms or agents is not available. Lack of training on what to do when terrorists strike using biological agents can cumulatively increase the lethal effects of such agents. Molecular techniques of identifying microorganisms to species level are as promising as they are time-consuming, while technical expertise and a conducive environment for managing such equipment are mostly not available in the African setting. The governments in Africa as a matter of urgency should provide an atmosphere where the teaming population of people without jobs are employed, while hospitals are adequately equipped, and training of health workers on what to do immediately after cases of terrorism are reported. The review highlights these agents and the diagnostic tools necessary to facilitate early response to bioterrorism. Keywords: Bioagents, Bioterrorism, Classification, Identification, Spread.